An analysis on the role of corporate identity on influencing company performance in the insurance sector in Zimbabwe. A case of NicozDiamond Insurance Limited. - Mariga, Blessing (Midlands State University, 2017)
The research was carried out to assess the role of corporate identity management on influencing company performance in the insurance industry. The objectives of this research were to establish the effectiveness of corporate design on insurance policy sale growth, to determine if corporate communication improves Gross Premium Written( GPW) and to find out if corporate behavior influences customer retention. These objectives were used to gather literature from several authors to get an appreciation of how corporate identity management affects company performance in the insurance industry in Zimbabwe. Areas of agreements and disagreements of different scholars were highlighted in the research. Exploratory and Descriptive research designs which applied to this research were discussed, justified and used to gather information pertaining to the research from NicozDiamond employees, management and employees from Harare and Gweru Branches. Sampling procedures and techniques were justified and explained by the researcher. The researcher used non-probability and probability sampling techniques. Interviews and questionnaires were used to by the researcher to gather data. Data gathered through these instruments was presented using tables, pie charts and graphs. The conclusions of the research were that corporate design affects policy sales growth, corporate behavior influences customer retention and corporate communication affects gross premium written in the insurance industry. However the researcher recommends that the company continuously upgrades its corporate design to counter competition, engage in ethical business practices and also continuously mange its communication with its diverse publics.